MANAJEMEN PENGELOLAAN SARANA DAN PRASARANA DI UNIT RAWAT INAP RUMAH SAKIT TENTARA KOTA PEKANBARU TAHUN 2025 - Maharani, Maudy; Candra, Leon; Widodo, M. Dedi (Journal of Hospital Administration and Management (JHAM), 2025)
Facilities and Infrastructure is a unit responsible for maintaining both medical and non-medical facilities, including minor repairs across all hospital buildings, covering architecture and utilities. The maintenance system in the Inpatient Unit of the Tentara Hospital in Pekanbaru is considered suboptimal, as seen from the facilities that are not suitable for use and the limited workforce in the facilities and infrastructure section which has an impact on the effectiveness of services and the safety of using medical equipment.. This study aims to examine the management of facilities and infrastructure in the Inpatient Unit of the Tentara Hospital Pekanbaru in 2025. The research uses a qualitative method with a case study approach, involving three informants. Data were collected through in-depth interviews, observation, and document review. The results show that manpower in the Hospital Facilities and Infrastructure Installation is still insufficient and not specifically assigned to handle facilities and infrastructure issues. Although the maintenance budget is available, there is no allocation for travel expenses. The absence of standard operating procedures results in inappropriate maintenance methods. Machine maintenance is routinely conducted on-site due to the lack of a workshop. Several inpatient room facilities such as air conditioners, toilets, and ceilings are poorly maintained, and spare parts for medical equipment remain incomplete. It is concluded that manpower does not meet the standard, and although the maintenance budget is sufficient, there are delays in fund disbursement. Some materials in inpatient rooms are not well-maintained, and medical equipment spare parts are still lacking. On-site machine maintenance continues due to the absence of a workshop. Maintenance procedures remain inadequate due to the lack of standard operating procedures. It is recommended that the hospital establish an Hospital Facilities and Infrastructure Installation organization, provide training, and build a workshop to optimize facility and infrastructure maintenance